A spatial optimization approach to increase the accuracy of rooftop solar energy assessments. (15th June 2022) - Zhong, Qing; Nelson, Jake R.; Tong, Daoqin; Grubesic, Tony H.
Highlights: A novel maximum cover location problem is developed for rooftop PV panel layout. High resolution images of three distinct rooftop structures are collected with a UAV. Rooftop structure, panel size, and irradiance determine optimal PV panel layout. Results highlight the importance of considering panel layout for energy estimates. The framework provides a spatially explicit optimized panel configuration for each rooftop. Abstract: Recent years have seen a substantial increase in energy produced by renewable sources. The International Energy Agency (IEA) expects a large portion of future growth in renewable energy to come from solar, especially rooftop photovoltaic (PV) systems. Studies focused on estimating rooftop solar energy potential generally use the total area available for PV installation as determined by solar irradiance availability. This process can lead to substantial over- or under-estimation of energy estimates. Only a few studies have incorporated the spatial layout of PV panels in the solar energy generation estimates, and none have simultaneously considered PV panel size, orientation, and rooftop structure. We address this limitation with a new spatially explicit optimization framework to enhance the accuracy of rooftop solar energy assessments. We consider both the roof's structural configuration and the shape and size of the panels in a novel maximum cover spatial optimization model. After applying the framework to three different types of rooftops (flat roof, pitched roof, and complex roof), we find that conventional methods can lead to a nearly 60% overestimation of energy potential compared to the optimized panel layout. Our work illustrates the importance of considering panel size and rooftop characteristics and offers a mechanism for designing more efficient rooftop PV systems.